URGENSI PENYESUAIAN KEBIJAKAN PENERIMAAN TAHANAN RUTAN KOTA BATAM PADA MASA ENDEMI COVID-19 - Karya So Immanuel Gort; Rufinus Hotmaulana Hutauruk; F. Yudi Priyo Amboro (Jurnal Komunikasi Hukum, 2022)
The high impact of COVID-19 requires the Government to issue a policy on limiting the number of prisoners. This study aims to find out the rules regarding the mechanism for accepting new prisoners by the Batam Detention Center due to the Covid-19 Pandemic, the impact of delays in accepting new prisoners by the Detention Center due to the Covid-19 Pandemic, the extent of readiness of law enforcement officers and policy concepts and solutions for accepting prisoners during endemic times. covid-19 by the Batam Rutan. This research method is normative juridical, with the results of receiving prisoners during the covid pandemic referring to the Decree of the Minister of Law and Human Rights, there have been restrictions on movement of prisoners, there has been a buildup of prisoners and during endemic times, Batam Detention Center only accepts registration and administration from the prosecutor's office and the police and started to enforce normal policies.